Synthesis of DNA dumbbell based inhibitors for the human DNA methyltransferase Dnmt1. - Kuch, D; Schermelleh, L; Manetto, S; Leonhardt, H; Carell, T (2008)
(Figure Presented) Dumbbells that block: Dnmt1 is a crucial enzyme in maintaining the methylation pattern of genes and as such is a critical element of the epigenetic programming process. DNA dumbbell constructs have been developed that inhibit Dnmt1 and have potential in the regulation of DNA methylation patterns in cells (see scheme; SAM=S-adenosylmethionine, Fl=Cy3 fluorescence label, CN=5-azadC, C-Me=5-methyldC). © 2008 Wiley-VCH Verlag GmbH and Co. KGaA.